Veiling in Fear or in Faith? Meanings of the Hijab to Practicing Muslim Wives and Husbands in USA. Issue 7 (3rd October 2017) - Alghafli, Zahra; Marks, Loren D.; Hatch, Trevan G.; Rose, Andrew H.
ABSTRACT: This article examines the Muslim practice of wearing the hijab —the veiling and covering of a woman's head and body. More specifically, this study aims to present insiders' perspectives regarding the personal understandings of the hijab among 20 wives and 20 husbands ( n  = 40) in religious Shia and Sunni Muslim families living in USA. Qualitative analysis yielded three emergent themes: (1) The hijab as a symbol of religious commitment; (2) the hijab as a tool of protection, rather than oppression, for women and families; and (3) two different views of Muslims' reasoning behind the hijab . These data suggest that, as perceived by "insider" participants, the hijab has perceived benefits for religious Muslim families, although counterexamples and concerns are also expressed.